The role of resveratrol in cellular aging - Daria Bieniek; Natalia Skierkowska; Monika Prylińska; Jakub Husejko; Małgorzata Gajos; Hanna Bednarek; Filip Biernacki; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Resveratrol is a substance present in grapes, blueberries and peanuts. Its concentration in grapes varies depending on the type and strain of the fruit. Resveratrol has a number of health-promoting properties for the body. Researchers most often indicate antioxidant, anticancer and cardioprotective activity, especially in the context of coronary heart disease, as well as anti-inflammatory, inhibiting the proliferation of pro-inflammatory cytokines. Resveratrol plays a neuroprotective role in the body, especially in the context of Alzheimer's disease, has a positive effect on the genes responsible for longevity and is the perpetrator of the so-called "The French paradox". The aim of the work was to present the role of resveratrol in cellular aging.